'Becoming the song': Alice Parker, community singing and unlearning choral strictures. Issue 1 (1st March 2022) - Palkki, Joshua
This article conveys research about participatory community singing that I explore through various lenses. I present thoughts and reflections from my interview with Alice Parker, who has many years of experience leading community singing events as well as ethnographic data collected from a monthly community singing event in the American Midwest. I analyse these data through the lens of a 'traditional' choral conductor who, prior to undertaking this investigation, had little knowledge about participatory singing traditions; I also utilize scholarship on the differences between participatory and presentational music activities. In our interview, Ms Parker drew on many years of experience in both areas to provide touchstones for facilitating community singing events and also the differences between these events and more traditional choral settings. Perhaps in reflecting on this dichotomy, facilitators of these two important forms of music making might learn from one another.